BUILDING TOGETHER: A reflection on community-based participatory research priorities in relation to hiv/aids in a remote region of Quebec - Labra, Oscar; Gingras Lacroix, Gabriel; Ependa, Augustin; Isabelle, Sylvie; Bedoya Mejia, Juan; Tremblay, Gilles; Giroux, Marie-Ève; Viau, Alexandre; Beaucage, Mélanie; Monteith, Kent; Bizot, Dominic; Bustinza, Ray; et al. (Canadian Social Work Review / Revue canadienne de service social, 2020)
The objective of the article is to underline the importance of community-based participatory research, which involves institutional researchers and community practitioners, in establishing local and regional research priorities in relation to HIV/AIDS. We describe an 11-month-long reflection process conducted by a research collective in the Abitibi-Témiscamingue region of northern Quebec. The significant results of the joint reflection and discussion process included: the development of local capacities for research and collective action, involving academics and practitioners; the valorization of participatory research; and the increased accessibility of research-based knowledge for community actors involved in the fight against HIV/AIDS. In contrast with more traditional research methods, the participatory approach situates the balance of power within a research collective that jointly determines, throughout the course of the project, the priorities that best reflect local needs for HIV/AIDS research. This initial process of discussion resulted also in the joint validation of a forthcoming grant application to be submitted to the Canadian Institutes of Health Research (CIHR).